Dynamics of Collaboration in Handling Sexual Violence Against Children in Batang Regency - Ledi Nabila Fikriyah; Kismartini Kismartini; Retno Sunu Astuti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The number of sexual violence against children in Batang Regency is quite high, so the Batang Government formed a collaboration with a special team consisting of the Women's Empowerment, Child Protection and Population Control Family Planning Service (DP3AP2KB), the Women and Children Protection Task Force (PPA), the Regional Leadership Coordination Forum (Forkopimda), the Indonesian Ulema Council (MUI), Community Leaders, and Regional Apparatus Organizations (OPD) in Batang Regency. The Batang Police also provides a Call Center 110 or directly visit the Criminal Investigation Unit of the Women and Children Protection Unit. The purpose of this article is to explain the collaboration process in handling sexual violence against children and the factors that influence it. This article uses the collaboration theory of Ansell & Gash and DeSave. The method used is descriptive qualitative with analysis of secondary sources such as journals, newspapers, and news websites. The results of the study indicate that the collaboration process in handling sexual violence against children in Batang Regency is good but not ideal and effective. There are inhibiting factors in the collaboration process, namely low commitment from several stakeholders, unclear procedures and inadequate resources.